MÜŞTERİ SÖZLEŞMELERİNDEN HASILATINÖZELLİKLİ DURUMLAR ÇERÇEVESİNDEDEĞERLENDİRİLMESİ - (:unkn) unknown (My University, 2019)
Uluslararası Muhasebe Standartları Kurulu, daha önceki hasılat standardının eksikleriningiderilmesi amacıyla 2014 yılında hasılatın muhasebeleştirilmesine yönelik yeni standardı“UFRS 15 – Müşteri Sözleşmelerinden Hasılat” olarak yayınlamıştır. Yeni standarttahasılatın muhasebeleştirilmesine yönelik 5 Aşamalı Model geliştirilmiş ve bu standart ilefarklı sektörler arasındaki tutarlılık ve karşılaştırılabilirliğin sağlanması hedeflenmiştir. Buçalışmada, yeni hasılat standardının önemli finansman bileşeninin varlığı, değişken bedel,indirimler ve iade hakkı, asıl-vekil değerlendirmesi ve garantiler gibi unsurlar açısından elealınması ve yeni standardın farklı açılardan daha iyi anlaşılmasına katkı sağlamakhedeflenmiştir.

In 2014, International Accounting Standards Board released the new standard on revenue recognition as “IFRS 15 – Revenue from Contracts with Customers” to overcome the deficiencies of current standard. It creates a five-step model for revenue recognition from contracts with customers and it is aimed that this new standard can promote consistency and comparability across different kinds of industries. This study examines the new revenue standard from the viewpoints of special issues; significant financing component, variable consideration, discounts and sales with a right of return, principal vs. agent consideration and warranties. It is expected that the study would contribute to the better understanding of the new standard by giving supportive examples.
ASSESSMENT OF REVENUE FROM CONTRACTS WITH CUSTOMERS WITHIN SPECIAL ISSUES